COMPETITIVE TENDERING: FAKTOR TERJADINYA INSOLVENCY PADA PERUSAHAAN KONSTRUKSI (SEBUAH LITERATUR) - Ipak Neneng Mardiah Bukit (Jurnal Teknik Sipil Unaya, 2015)
The construction industry is a vanguard in developing countries, including Indonesia. It has unique characteristics where complex works exist. These characteristics distinguish this industry from other industries in economy. Its project involves so many risks that have potentially business failure. Failure, bankruptcy or insolvency is unpleasant words, but people in the industry cannot ignore them. This paper thoroughly explored the causes of insolvency in Construction Company due the procedure of competitive tendering in Indonesia and how to avoid it. Insolvency in Indonesia is caused by lack of business experiences, country’s economic condition, poor control of cash flow, cannot convince clients, and low profit margin as a result of competitive tendering. Some researchs found that insolvency can be predicted at early opportunity, and some methods are applied to prevent insolvency.